Dielectric properties of epoxy–barium titanate composite for 5 GHz microstrip antenna design - Nurulfadzilah, Hassan; Nurul Hazlina, Noordin; Mohamad Shaiful, Abdul Karim; Mohd Ruzaimi, Mat Rejab; Ma, Quan Jin (Springer Nature, 2019)
To fulfill the demands for robust, compact microstrip antenna for wireless communication, miniaturization is necessary. To achieve this, conventional dielectric microstrip antenna substrate can be replaced with high-permittivity composite dielectric material. Epoxy–barium titanate composite has potential to be used as antenna substrate. This paper focuses on fabrication of epoxy–barium titanate composite at different filler loadings. Then, the permittivity of the composite at G-band frequencies (4–6 GHz) is measured using waveguide technique. The effect of filler concentration to permittivity is observed at 5 GHz, the intended resonant frequency of the antenna. Waveguide technique determines the complex permittivity by analyzing only the measured transmission coefficient of the material, and easily noise affected reflection coefficient is not used. The experimental results show that the permittivity of epoxy–barium titanate increases steadily as the filler volume increases. At the highest filler volume (20%), the permittivity of the composite at 5 GHz is at 6.67. The results obtained are in good agreement with theoretically predicted values.